**Answers:**

7-5=sqrt(P+3)

2=sqrt(P+3)

squaring both sides of the equation: 2^2 =P+3

4=P+3

4-3=P

1=P

First, add the sqrt part to both sides and subtract 5 from both sides to get 2 = sqrt(P+3)

Then square both sides which cancels out the sqrt on the right, and makes the 2 become 4: 4 = P+3

Then subtract 3 from both sides and you have it.

7-sqrt(p+3)=5

so -sqrt(p+3)=5-7

-sqrt(p+3)=-2

If you divide by -1 then

sqrt(p+3)=2

then square both sides.

p+3=4 then

p=1

7 - sqrt(P+3)=5

- sqrt(P+3)= -2 x -1

(sqrt(P+3))^2=2^2

P+3=4

P=4-3

P=1

This article contents is post by this website user, EduQnA.com doesn't promise its accuracy.

**More Questions & Answers...**